PEMANFAATAN SMS GATEWAY DENGAN GAMMU DAN WEBCAM BERBASIS VISUAL BASIC 6.0 PADA SISTEM KEAMANAN RUMAH - Islahuddin, Muhammad Ishaq; Subari, Arkhan (Gema Teknologi, 2013)
Muhammad Ishaq Islahuddin, Arkhan Subari, in this paper explain that in a home security system is very important information dissemination system. One of them by the use of SMS Gateway. By using Gammu and MySQL as a database and use a webcam as a tool for monitoring room in the house. The way this system works is a home security system using a PIR sensor detecting human movement. After that, if the data from the sensors in the microcontroller. Microcontroller then sends the data to a computer through a serial port. On the computer there is a VB 6.0 application. when the PIR sensor detects the presence of a human, the computer will be otomstis capture and send SMS alerts to a database of numbers that have been stored. Keywords : Webcam, SMS Gateway, Gammu, MySQL, Visual Basic 6.0 .